PERAN GURU PAI DALAM PEMBENTUKAN KARAKTER SISWA KELAS X BISNIS RITAIL SMK NEGERI 1 KOTABUMI - Rukayah, Siti; Setyoningsih , Sri; Patimah, Siti; Afifatun , Siti; Arung Arafah, Latief (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2024)
This research is motivated by the number of delinquency among students. The purpose of this study is to look at the role of PAI teachers as educators in shaping student character. This research uses qualitative methods of field study research. With the subject of 6 respondents. Data collection techniques in this study used observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation and conclusion drawing.The results showed that the role of PAI teachers in the formation of student character is needed by students because the presence of PAI teachers who act as parents of students certainly has a very large role in order to educate students to become ihsani humans. The role of PAI teachers in the formation of student character includes: Empowerment, exemplary, intervention, integrated, sekrening. The strategies carried out by PAI teachers in the formation of student character include: Habituation of 3S (Greetings, greetings, smiles), Habituation of dhuha and dzuhur prayers in congregation, Habituation of reading short letters, recitation of prayers, Habituation of being disciplined, Habituation of being honest. The supporting factors come from external factors, namely good pedagogical and professional competence of teachers, creativity in the implementation of learning. Inhibiting factors consist of internal factors, namely from the person of each learner due to the lack of education and parental guidance given to children since childhood and external factors external factors are one of the inhibiting factors from outside the city community environment which is acu acu to various kinds of problems that exist in students, even though society is a continued education from the school level, because the community environment is usually called non-formal education is also very influential on student life, especially in the formation of student character.